Nature-inspired flow-fields and water management for PEM fuel cells - Cho,JIS; Neville,T; Trogadas,P; Wu,B; Brett,D; Coppens,MO (2018)
Flow-field design is crucial to polymer electrolyte membrane fuel cell (PEMFC) performance, since non-uniform transport of species to and from the membrane electrode assembly (MEA) results in significant power losses[1]. The long channels of conventional serpentine flow-fields cause large pressure drops between inlets and outlets, thus large parasitic energy losses and low fuel cell performance[2]. Here, a lung-inspired approach is used to design flow fields guided by the structure of a lung. The fractal geometry of the human lung has been shown to ensure uniform distribution of air from a single outlet (trachea) to multiple outlets (alveoli). Furthermore, the human lung transitions between two flow regimes: 14-16 upper generations of branches dominated by convection, and 7-9 lower generations of space-filling acini dominated by diffusion[3,4]. The upper generations of branches are designed to slow down the gas flow to a rate compatible with the rate in the diffusional regime (Pé ~ 1)[5], resulting in uniform distribution of entropy production in both regimes[3,4]. By employing a three-dimensional (3D) fractal structure as flow field inlet channel, we aim to yield similar benefits from replicating these characteristics of the human lung. The fractal pattern consists of repeating “H” shapes where daughter “H's” are located at the four tips of the parent “H”. The fractal geometry obeys Murray's law, much like the human lung, hereby leading to minimal mechanical energy losses. Furthermore, the three-dimensional branching structure provide uniform local conditions on the surface of the catalyst layer as only the outlets of the fractal inlet channel are exposed to the MEA. Numerical simulations were conducted to determine the number of generations required to achieve uniform reactant distribution and minimal entropy